Protective effect of Hylocereus monocanthus on carbon tetrachloride-induced acute hepatotoxicity in rats - Alfaro-Ayvar, Janet Rocio (2022)
The fruits of Hylocereus monacanthus is considered a promising source of natural antioxidants and are therefore considered a functional and nutraceutical food. The objective of this study was to determine the hepatoprotective activity of ethanolic extract of Hylocereus monacanthus (EEtH) in albino rats with acute carbon tetrachloride-induced toxicity. Phytochemical analysis showed that the fruit of Hylocereus monacanthus contains phenols, flavonoids, among other secondary metabolites; the hepatoprotective activity was evaluated through the biochemical assay of albumin (ALB), direct bilirubin (BD), indirect bilirubin (BI), total bilirubin (BT), alkaline phosphatase (FAL), globulins (GLOB), total proteins (PT) and glutamic oxalacetic transaminase (TGO) in serum and a histopathological study. Treatment with EEtH in albino rats with CCl4-induced hepatotoxicity maintained decreased values of FAL, TGO, BT, BD, BI activity; while PT value remained increased; however, ALB and GLOB values did not undergo significant changes and protected histopathological changes from CCl4. It is concluded that EEtH has a potent hepatoprotective effect on toxic-metabolic lesions such as those caused by CCl4 in albino rats, and this is due to its high antioxidant activity.